2020
DOI: 10.3390/ijerph17041273
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Assessment of Tap Water Following the 2016 Louisiana Flooding

Abstract: Floods are a prominent risk factor in the world of public health, as there is a risk of dispersal of harmful biological and chemical contaminants in floodwater. As climate change increases, the occurrence of natural disasters and risk of adverse health outcomes due to flash flooding also increases. Fecal indicator bacteria, such as Escherichia coli and Enterococci, are often encountered in contaminated floodwater and can cause gastrointestinal illnesses as well as a variety of infections. In August 2016, East … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…being not detected in CZ_0728. Therefore, the rising risk of waterborne pathogens in post-flush tap water samples indicates that extreme rainfall events are a prominent risk factor in public health in terms of water (and food) safety (Phan and Sherchan, 2020). To maintain the standard of the treated discharge water during extreme rainfall events in the future, the government needs to invest more to upgrade the water processing capacity of wastewater treatment plants to be prepared for unpredictable effluent load.…”
Section: Potential Environmental Drivers: Extreme Precipitation and H...mentioning
confidence: 99%
“…being not detected in CZ_0728. Therefore, the rising risk of waterborne pathogens in post-flush tap water samples indicates that extreme rainfall events are a prominent risk factor in public health in terms of water (and food) safety (Phan and Sherchan, 2020). To maintain the standard of the treated discharge water during extreme rainfall events in the future, the government needs to invest more to upgrade the water processing capacity of wastewater treatment plants to be prepared for unpredictable effluent load.…”
Section: Potential Environmental Drivers: Extreme Precipitation and H...mentioning
confidence: 99%
“…Moreover, no study to date has investigated the impact of Hurricane Hanna on the microbial contamination in receiving waters in rural areas. In molecular analysis, HF183 is the most commonly used human fecal marker in water; , however, very few studies investigated the occurrence of human Bacteroides in GW following hurricanes. , Additionally, similar studies have reported different relationships between culturable methods and qPCR for the quantification of Escherichia coli, which need further clarifications.…”
Section: Introductionmentioning
confidence: 99%